1989
DOI: 10.1007/bf00274002
|View full text |Cite
|
Sign up to set email alerts
|

Is there a correlation between morphological and cytogenetic findings in placental tissue from early missed abortions?

Abstract: A retrospective study of 200 missed abortions was performed to determine whether morphological criteria alone are sufficient to ascertain a chromosomal aetiology. Placental changes were classified into five morphological and four morphometric groups, according to the severity of alterations, and were then correlated with the cytogenetic data. The rate of chromosome anomalies was approximately 50% and was thus not significantly different within the groups II-V, but it was 80% in group I, which covered the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(8 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“…This findings is in contrast to the estimated male:female sex ratio of 1.8 or 1.3 calculated from long-term culture of chorionic villi [14,19], but it corresponds with the sex ratio of 0.7 obtained by direct preparation method of the same tissue [15]. One can say that this altered sex ratio is due to maternal cell contamination.…”
Section: Discussioncontrasting
confidence: 52%
“…This findings is in contrast to the estimated male:female sex ratio of 1.8 or 1.3 calculated from long-term culture of chorionic villi [14,19], but it corresponds with the sex ratio of 0.7 obtained by direct preparation method of the same tissue [15]. One can say that this altered sex ratio is due to maternal cell contamination.…”
Section: Discussioncontrasting
confidence: 52%
“…Monosomy of autosomes is an extremely rare finding in first-trimester miscarriages accounting for 0.22-0.85% of all observed chromosomal abnormalities [Hassold et al, 1980;Guerneri et al, 1987;Rehder et al, 1989]. It is suggested that the overwhelming majority of monosomic zygotes are eliminated before implantation.…”
Section: Effects Of Origin and Tissue-specific Distribution Of Autosomentioning
confidence: 99%
“…(1) meiotic errors are prevalent in the etiology of trisomies for chromosome 3, 6, 9, 10, 12, 13, 14, 16, 18, 20, 21, and 22; (2) mitotic errors are prevalent in the etiology of trisomies 2 and 17; Eiben et al [1990]; Griffin et al [1997]; Guerneri et al [1987]; Hassold et al [1980]; Kajii et al [1980]; Meulenbroeck and Geraedts [1982]; Minelli et al [1993]; Ohno et al [1991]; Rehder et al [1989]; Takahara et al [1977]; Warburton et al [1978].…”
Section: Evidence For Tissue-specific Distribution Of Autosomal Trisomentioning
confidence: 99%
“…The diploid/tetraploid molar cases are not different histologically from the trip loid partial moles in our series, and correspond to group 1 according to the classification of Rehder et al [17], whereas the tetraploid non-mosaic placentas represent gradations between the hydropic abortuses and partial moles (group 2). There has been one patient who received monochemotherapeutic treatment among these partial moles.…”
Section: Discussionmentioning
confidence: 93%